Biodiversity and extinction accounting for sustainable development: A systematic literature review and future research directions. (19th October 2020) - Roberts, Lee; Hassan, Abeer; Elamer, Ahmed; Nandy, Monomita
Abstract: This paper seeks to present the first systematic literature review (SLR) on biodiversity and species extinction accounting publications. This strand of research is gaining increased attention due to emerging scientific evidence that finds a relationship between the human destruction of biodiversity and the recent Covid‐19 crisis, causing profound economic and health impacts. This justifies the need for an SLR of 40 articles from 2013 to 2020. Descriptive results show research contributions peaked in 2018 with the most publications appearing in the Accounting, Auditing & Accountability Journal. Results show legitimacy theory is the most applied theoretical framework with global studies and developed country specific research receiving the greatest attention. In addition, content analysis is identified as the preferred research methodology. Additionally, through synthesising and analysing literature, we provide potential opportunities for future research that is underexplored. This paper will provide a valuable study for academics, policymakers and practitioners pursuing research in this field.